The Short Warwick-Edinburgh Mental Well-being Scale (SWEMWBS): an Italian validation using confirmatory factor analysis and Rasch analysis - Paolo Soraci; Nadia Bevan; Mark D. Griffiths; Renato Pisanti; Rocco Servidio; Ambra Ferrari; Carla Di Bernardo; Amir H. Pakpour (BMC Psychology)
Abstract The present study examined the psychometric properties of the Short Warwick-Edinburgh Mental Well-being Scale (SWEMWBS). A total of 742 Italian participants (84.6% female), with a mean age of 33.08 years (SD = 12.44) took part in a cross-sectional survey study. Confirmatory factor analysis and Rasch analysis were used to examine the psychometric properties. The CFA showed that the SWEMWBS had a unidimensional structure with robust psychometric properties and showed good internal consistencies (Cronbach’s alpha 0.88; McDonald’s omega 0.91). Overall, most items showed no substantial differential item functioning in the Rasch analysis, except for Item 7, indicating that female participants reported more difficulty with this item than the male participants. The SWEMWBS was positively associated with life satisfaction and negativity associated with general psychological distress (i.e., anxiety, stress, and depression). In sum, the SWEMWBS showed robust psychometric properties capable of assessing positive aspects of mental health and well-being among Italian-speaking adults.